Traumatic andropause after combat injury. (28th August 2015) - Jones, Gareth Huw; Kirkman-Brown, Jackson; Sharma, Davendra Murray; Bowley, Douglas
Abstract : In association with lower extremity amputation, complex genitourinary injuries have emerged as a specific challenge in modern military trauma surgery. Testicular injury or loss has profound implications for the recovering serviceman, in terms of hormone production and future fertility. The initial focus of treatment for patients with traumatic testicular loss is haemostasis, resuscitation and management of concurrent life-threatening injuries. Multiple reoperations are commonly required to control infection in combat wounds; in a review of 300 major lower extremity amputations, 53% of limbs required revisional surgery, with infection the commonest indication. Atypical infections, such as invasive fungal organisms, can also complicate military wounding. We report the case of a severely wounded serviceman with complete traumatic andropause, whose symptomatic temperature swings were initially mistaken for signs of occult sepsis.